Development of RFLP-PCR method for the identification of medically important Aspergillus species using single restriction enzyme MwoI - Diba, K.; Mirhendi, H.; Kordbacheh, P.; Rezaie, S. (Brazilian journal of microbiology, 2014)
In this study we attempted to modify the PCR-RFLP method using restriction enzyme MwoI for the identification of medically important Aspergillus species. Our subjects included nine standard Aspergillus species and 205 Aspergillus isolates of approved hospital acquired infections and hospital indoor sources. First of all, Aspergillus isolates were identified in the level of species by using morphologic method. A twenty four hours culture was performed for each isolates to harvest Aspergillus mycelia and then genomic DNA was extracted using Phenol-Chloroform method. PCR-RFLP using single restriction enzyme MwoI was performed in ITS regions of rDNA gene. The electrophoresis data were analyzed and compared with those of morphologic identifications. Total of 205 Aspergillus isolates included 153 (75%) environmental and 52 (25%) clinical isolates. A. flavus was the most frequently isolate in our study (55%), followed by A. niger 65(31.7%), A. fumigatus 18(8.7%), A. nidulans and A. parasiticus 2(1% each). MwoI enabled us to discriminate eight medically important Aspergillus species including A. fumigatus, A. niger, A. flavus as the most common isolated species. PCR-RFLP method using the restriction enzyme MwoI is a rapid and reliable test for identification of at least the most medically important Aspergillus species.